Defining “Public or General Importance”: An Analytical Study of Special Leave to Appeal Granted by the Supreme Court of Sri Lanka in Terms of Article 128(2) of the Constitution - Asindu Munasinghe, H.M.; Anushi, W. (Faculty of Arts, University of Jaffna & Surana and Surana International Attorneys, 2026)
Under Article 128(2), the Supreme Court may, in its discretion, grant special leave to appeal to itself from a judgment of the Court of Appeal, only when in its opinion that the case or matter is fit for review by the Supreme Court. However, the proviso to the said provision emphasizes that, when the court is satisfied that “the question to be decided is of public or general importance”, the Court shall grant leave to appeal in such every matter or proceedings. Though the Supreme Court has granted Special Leave to Appeal in many cases specifying that the matter is of general or public importance, no criteria or guideline has been identified to determine whether a matter is of public or general importance. This gap remains a lacuna in the legal jurisprudence and this paper aims to answer this gap. Many comparative jurisdictions provide some useful interpretations. English courts have been determined that, if the matter involves the elucidation of Public Law by higher courts, the matter is of importance to a general class and that the matter touches on a department of State, or the State itself, in relation to policies that are of general importance. South African courts have been adopted the position that by assessing whether it deeply affects the public and requires the Constitutional Court’s elucidation of the law. The Constitutional Court evaluates whether lower courts have properly advanced the law and whether their decisions benefit the public at large by promoting constitutional values, ensuring that the application of these values benefits a broad spectrum of people rather than a few, thus aligning with the common good. Accordingly, this paper proposes that, if a matter significantly affects public interest with wider legal consequences and the outcome contributes meaningfully to the common good such a matter is of public or general importance.
Keywords: Article 128(2) of the constitution; Special leave to appeal; Public or general importance